Composition for forming protective film having a diol structure
By using a protective film composition formed by combining a crosslinking agent and a surfactant with a compound containing adjacent hydroxyl groups in the molecule, the problem of insufficient resistance of the resist underlayer film in wet etching and dry etching is solved, and effective protection of the semiconductor substrate and efficient etching process are achieved.
Patent Information
- Application Number
- CN201880082023.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-12-22
- Filing Date
- 2018-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-09-19
AI Technical Summary
In semiconductor manufacturing, the resist lower layer film has insufficient resistance to the wet etching liquid during wet etching, and it is difficult to remove quickly during dry etching, resulting in damage to the substrate.
A protective film composition comprising at least one group of 2 hydroxyl groups adjacent to each other in the molecule or a polymer thereof, and a crosslinking catalyst, a crosslinking agent and a surfactant are added thereon to form a protective film that is resistant to wet etching liquid and can be quickly dry-etched.
Good resistance to the wet etching liquid for semiconductors is achieved, and the resist underlayer film can be quickly removed during dry etching to avoid damage to the substrate.
Smart Images

Figure BDA0002545869450000021 
Figure BDA0002545869450000041 
Figure BDA0002545869450000071
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for forming a protective film having excellent resistance to a semiconductor wet etching solution, preferably an alkaline hydrogen peroxide solution, in a photolithography process in semiconductor manufacturing, and also relates to a method for forming a resist pattern using the protective film and a method for manufacturing a semiconductor device. Background Art
[0002] In semiconductor manufacturing, a photolithography process is well known in which a resist underlayer film is provided between a substrate and a resist film formed thereon to form a resist pattern of a desired shape.
[0003] Patent Document 1 discloses an antireflective coating composition for use with an overcoated photoresist, which contains a polymer having a glycidyl group and a polymer having an aromatic group substituted with a hydroxyl group or the like, and a method for forming a photoresist underlayer film therefrom and performing exposure, development, and patterning.
[0004] Patent Document 2 discloses a method of forming a photoresist relief image by coating a composition containing a resin having an epoxy reactive group such as a hydroxyl group and a crosslinking resin containing an epoxy group on a substrate and forming a photoresist layer thereon.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-107185
[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-187764 Summary of the invention
[0009] Problems to be solved by the invention
[0010] When the base substrate is processed by wet etching using the resist underlayer film as an etching mask, the resist underlayer film is required to have a good masking function for the wet etching solution during the base substrate processing. Furthermore, when the unnecessary resist underlayer film is removed by dry etching after the wet etching, in order not to damage the base substrate, the resist underlayer film is required to have a high etching speed (high etching rate) so that it can be quickly removed by dry etching.
[0011] Conventionally, in order to develop resistance to SC-1 (ammonia-hydrogen peroxide solution) which is a type of wet etching solution, a method of using gallic acid as an additive has been used.
[0012] Furthermore, it is known that a catechol structure shows an effect of improving resistance to wet etching solutions for semiconductors (Patent Documents 1 and 2), but since it contains an aromatic group, it is difficult to achieve both a high etching rate and a high etching rate.
[0013] An object of the present invention is to solve such problems.
[0014] Means for solving problems
[0015] The present invention includes the following aspects.
[0016] [1] A composition for forming a protective film resistant to a wet etching solution for semiconductors, comprising: a compound having at least one set of two adjacent hydroxyl groups in a molecule, or a polymer thereof; and a solvent.
[0017] [2] The protective film-forming composition according to [1], wherein the two adjacent hydroxyl groups are 1,2-ethylene glycol structures.
[0018] [3] The protective film-forming composition according to [1], wherein the compound includes a partial structure represented by formula (1) or formula (2).
[0019]
[0020] (In formula (1) and formula (2), R 1 , R 2 and R 3 Each of them is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms which may be substituted, or an aryl group having 6 to 40 carbon atoms which may be substituted, and R 1 Can be used with R 2 or R 3 Together they form a ring, Z 1 and Z 2 represents a monovalent organic group. )
[0021] [4] The protective film-forming composition according to [3], wherein in the above formula (1) and formula (2), R 1 , R 2 and R 3 A hydrogen atom.
[0022] [5] The protective film-forming composition according to any one of [1] to [4], further comprising a crosslinking catalyst.
[0023] [6] The protective film-forming composition according to any one of [1] to [5], further comprising a crosslinking agent.
[0024] [7] The protective film-forming composition according to any one of [1] to [6], further comprising a surfactant.
[0025] [8] A protective film, characterized by being a fired product of a coating film formed from the protective film-forming composition according to any one of [1] to [7].
[0026] [9] A method for manufacturing a substrate with a resist pattern, characterized in that it includes a step of applying the protective film composition described in any one of [1] to [7] on a semiconductor substrate and firing it to form a protective film as a resist underlayer film, and is used for the manufacture of a semiconductor.
[0027]
[10] A method for manufacturing a semiconductor device, comprising the following steps: forming a protective film on a semiconductor substrate having an inorganic film formed on its surface using the protective film-forming composition described in any one of [1] to [7], forming a resist pattern on the protective film, dry-etching the protective film using the resist pattern as a mask to expose the surface of the inorganic film or the semiconductor substrate, and wet-etching and washing the inorganic film or the semiconductor substrate using a semiconductor wet etching solution using the dry-etched protective film as a mask.
[0028] Effects of the Invention
[0029] In the present invention, by introducing a 1,2-ethylene glycol structure which is an aliphatic group into the polymer, it is possible to exhibit not only resistance to a semiconductor wet etching solution but also a high etching rate. DETAILED DESCRIPTION
[0030] [Protective film forming composition]
[0031] The composition for forming a protective film resistant to a wet etching solution for semiconductors according to the present invention comprises: a compound containing at least one set of two adjacent hydroxyl groups in a molecule, or a polymer thereof; and a solvent.
[0032] [Compound containing at least one set of two adjacent hydroxyl groups in the molecule]
[0033] The two adjacent hydroxyl groups are preferably a 1,2-ethylene glycol structure.
[0034] Such a 1,2-ethylene glycol structure is preferably a partial structure represented by formula (1) or formula (2).
[0035]
[0036] (In formula (1) and formula (2), R 1 , R 2 and R 3 Each of Z is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms which may be substituted, or an aryl group having 6 to 40 carbon atoms which may be substituted, 1 and Z 2Represents a monovalent organic group, R 1 Can be used with R 2 or R 3 Together they form a ring.)
[0037] Examples of the alkyl group having 1 to 10 carbon atoms which may be substituted include methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, 1-methyl-cyclopropyl, 2-methyl-cyclopropyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, cyclopentyl, 1-methyl-cyclobutyl, 2- Methyl-cyclobutyl, 3-methyl-cyclobutyl, 1,2-dimethyl-cyclopropyl, 2,3-dimethyl-cyclopropyl, 1-ethyl-cyclopropyl, 2-ethyl-cyclopropyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1 -ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, cyclohexyl, 1-methyl-cyclopentyl, 2-methyl-cyclopentyl, 3-methyl-cyclopentyl, 1-ethyl-cyclobutyl, 2-ethyl-cyclobutyl, 3-ethyl-cyclobutyl, 1,2-dimethyl-cyclobutyl, 1,3-dimethyl-cyclobutyl, 2,2-dimethyl-cyclobutyl, 2,3- Dimethyl-cyclobutyl, 2,4-dimethyl-cyclobutyl, 3,3-dimethyl-cyclobutyl, 1-n-propyl-cyclopropyl, 2-n-propyl-cyclopropyl, 1-isopropyl-cyclopropyl, 2-isopropyl-cyclopropyl, 1,2,2-trimethyl-cyclopropyl, 1,2,3-trimethyl-cyclopropyl, 2,2,3-trimethyl-cyclopropyl, 1-ethyl-2-methyl-cyclopropyl, 2-ethyl-1-methyl-cyclopropyl, 2-ethyl-2-methyl-cyclopropyl and 2-ethyl-3-methyl-cyclopropyl, etc.
[0038] Examples of the aryl group having 6 to 40 carbon atoms include phenyl, o-methylphenyl, m-methylphenyl, p-methylphenyl, o-chlorophenyl, m-chlorophenyl, p-chlorophenyl, o-fluorophenyl, p-fluorophenyl, o-methoxyphenyl, p-methoxyphenyl, p-nitrophenyl, p-cyanophenyl, α-naphthyl, β-naphthyl, o-biphenyl, m-biphenyl, p-biphenyl, 1-anthryl, 2-anthryl, 9-anthryl, 1-phenanthryl, 2-phenanthryl, 3-phenanthryl, 4-phenanthryl and 9-phenanthryl.
[0039] Examples of the substituents of these alkyl groups and aryl groups include, but are not limited to, halogen atoms (fluorine, chlorine, bromine, and iodine), nitro groups, cyano groups, amino groups, hydroxyl groups, carbonyl groups, and carbonyloxy groups.
[0040] In formula (1) and formula (2), R 1 , R 2 and R 3 Preferred is a hydrogen atom.
[0041] [Monovalent organic group]
[0042] The monovalent organic group is not particularly limited and may be a group derived from various polymers or oligomers or a group derived from a low molecular weight compound.
[0043] [Monovalent organic group derived from polymer]
[0044] By using an organic group derived from a polymer, the dry etching rate (reduction in film thickness per unit time), extinction coefficient, refractive index, etc. of the resist underlayer film formed from the protective film-forming composition of the present invention can be adjusted.
[0045] The polymer is not particularly limited, and various organic polymers can be used, for example, addition polymers and condensation polymers such as polyester, polystyrene, polyimide, acrylic polymer, methacrylic polymer, polyvinyl ether, phenol novolac, naphthol novolac, polyether, polyamide, polycarbonate, and ring-opening polymerized polymers can be used.
[0046] Examples of such organic polymers include addition polymers containing addition polymerizable monomers such as benzyl acrylate, benzyl methacrylate, phenyl acrylate, naphthyl acrylate, anthracene methacrylate, anthracene methyl methacrylate, styrene, hydroxystyrene, benzyl vinyl ether and N-phenylmaleimide as structural units; and condensation polymers such as phenol novolac and naphthol novolac.
[0047] When an addition polymer is used as the organic polymer, the polymer may be a homopolymer or a copolymer. Addition polymers are produced using addition polymerizable monomers. Examples of such addition polymerizable monomers include acrylic acid, methacrylic acid, acrylate compounds, methacrylate compounds, acrylamide compounds, methacrylamide compounds, vinyl compounds, styrene compounds, maleimide compounds, maleic anhydride, and acrylonitrile.
[0048] Examples of the acrylate compound include methyl acrylate, ethyl acrylate, n-hexyl acrylate, isopropyl acrylate, cyclohexyl acrylate, benzyl acrylate, phenyl acrylate, anthracenemethyl acrylate, 2-hydroxyethyl acrylate, 3-chloro-2-hydroxypropyl acrylate, 2-hydroxypropyl acrylate, 2,2,2-trifluoroethyl acrylate, 2,2,2-trichloroethyl acrylate, 2-bromoethyl acrylate, 4-hydroxybutyl acrylate, 2-methoxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-methyl-2-adamantyl acrylate, 5-acryloyloxy-6-hydroxynorbornene-2-carboxylic acid-6-lactone, 3-acryloyloxypropyltriethoxysilane, and glycidyl acrylate.
[0049] Examples of the methacrylate compound include methyl methacrylate, ethyl methacrylate, n-hexyl methacrylate, isopropyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, phenyl methacrylate, anthracene methyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2,2,2-trifluoroethyl methacrylate, 2,2,2-trichloroethyl methacrylate, 2-bromoethyl methacrylate, 4-hydroxybutyl methacrylate, 2-methoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, 2-methyl-2-adamantyl methacrylate, 5-methacryloyloxy-6-hydroxynorbornene-2-carboxylic acid-6-lactone, 3-methacryloyloxypropyltriethoxysilane, glycidyl methacrylate, 2-phenylethyl methacrylate, hydroxyphenyl methacrylate, and bromophenyl methacrylate.
[0050] Examples of the acrylamide compound include acrylamide, N-methylacrylamide, N-ethylacrylamide, N-benzylacrylamide, N-phenylacrylamide, N,N-dimethylacrylamide, and N-anthrylacrylamide.
[0051] Examples of the methacrylamide compound include methacrylamide, N-methyl methacrylamide, N-ethyl methacrylamide, N-benzyl methacrylamide, N-phenyl methacrylamide, N,N-dimethyl methacrylamide, and N-anthryl acrylamide.
[0052] Examples of the vinyl compound include vinyl alcohol, 2-hydroxyethyl vinyl ether, methyl vinyl ether, ethyl vinyl ether, benzyl vinyl ether, vinyl acetic acid, vinyltrimethoxysilane, 2-chloroethyl vinyl ether, 2-methoxyethyl vinyl ether, vinylnaphthalene, and vinylanthracene.
[0053] Examples of the styrene compound include styrene, hydroxystyrene, chlorostyrene, bromostyrene, methoxystyrene, cyanostyrene, and acetylstyrene.
[0054] Examples of the maleimide compound include maleimide, N-methylmaleimide, N-phenylmaleimide, N-cyclohexylmaleimide, N-benzylmaleimide, and N-hydroxyethylmaleimide.
[0055] When a polycondensate is used as the polymer, examples of such a polymer include a polycondensate of a diol compound and a dicarboxylic acid compound.
[0056] Examples of the diol compound include diethylene glycol, 1,6-hexanediol, and butanediol.
[0057] Examples of the dicarboxylic acid compound include aliphatic dicarboxylic acids and aromatic dicarboxylic acids such as succinic acid, 2,2-dimethylsuccinic acid, adipic acid, terephthalic acid, isophthalic acid, phthalic acid, 3,3′-dithiodipropionic acid, tartaric acid, malic acid, and maleic anhydride.
[0058] Other examples include polyesters such as poly(1,2,4,5-pyromellitimide), poly(p-phenylene terephthalamide), polybutylene terephthalate, and polyethylene terephthalate, polyamides, and polyimides.
[0059] When a ring-opening polymer is used as the polymer, examples of such a polymer include condensation products of a diepoxy compound and a dicarboxylic acid compound.
[0060] Examples of the diepoxy compound include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and compounds such as the compounds shown in the following [3-1] to [3-16].
[0061]
[0062]
[0063] Examples of the dicarboxylic acid compound include the dicarboxylic acid compounds described above.
[0064] As the polymer, a polymer having a weight average molecular weight of, for example, 1,000 to 100,000, 1,500 to 50,000, 2,000 to 30,000, or 3,000 to 20,000 can be used.
[0065] It is preferred that the polymer has a structure of formula (10).
[0066]
[0067] (In formula (10), A represents a direct bond or -C(=O)-, and Ar represents a benzene ring, a naphthalene ring, or an anthracene ring which may be substituted with an alkyl group having 1 to 6 carbon atoms, a halogen atom, a hydroxyl group, a carboxyl group, an amino group, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 6 carbon atoms, a cyano group, an acetyl group, an acetoxy group, an alkoxycarbonyl group having 1 to 6 carbon atoms, a nitro group, a nitroso group, an amide group, an imide group, an alkoxysulfonyl group having 1 to 6 carbon atoms, or a sulfonamide group.)
[0068] It should be noted that, as the alkyl group in formula (10), there may be mentioned a methyl group, an ethyl group, a n-butyl group, a tert-butyl group, an isopropyl group, a cyclohexyl group and the like; as the halogen atom, there may be mentioned a fluorine atom, a chlorine atom, a bromine atom and an iodine atom; as the alkoxy group, there may be mentioned a methoxy group, an ethoxy group, a butoxy group and the like; as the alkylthio group, there may be mentioned a methylthio group, an ethylthio group, a butylthio group and the like; as the alkoxycarbonyl group, there may be mentioned a methoxycarbonyl group, an ethoxycarbonyl group, an isopropoxycarbonyl group and the like; as the alkoxysulfonyl group, there may be mentioned a methoxysulfonyl group, an ethoxysulfonyl group and the like.
[0069] The above polymer can be produced by the method described in Japanese Patent No. 5041175, for example.
[0070] It should be noted that, depending on the required etching rate, it is desirable to suppress the content of the aromatic group in the polymer to a certain level.
[0071] [Monovalent organic group derived from low molecular weight compound]
[0072] The low molecular weight compound from which the monovalent organic group is derived is also not particularly limited, but in consideration of the risk of volatilization during firing, the molecular weight is preferably 300 or more. The upper limit of the molecular weight is, for example, 999. Some preferred specific examples are as follows. * indicates a bond.
[0073]
[0074]
[0075] Furthermore, the monovalent organic group may be a group in which a spacer group is added to the above-mentioned low molecular weight compound.
[0076] Examples of the spacer group include -CH-, -(CH2) n -(n=1 to 20), -CH=CH-, -CH≡CH-, -N=N-, -NH-, -NHR-, -NHCO-, -NRCO-, -S-, -COO-, -O-, -CO-, -CH=N- and phenylene, or a combination of two or more thereof. Two or more of these spacers may be linked together.
[0077] [Specific examples of preferred compounds having a partial structure represented by formula (1)]
[0078] Preferred examples of compounds having a partial structure represented by formula (1) are as follows.
[0079] Examples of the polymer having a partial structure represented by formula (1) include structural units represented by the following formulae (A-1) to (A-12).
[0080]
[0081] In the polymer having a partial structure represented by formula (1) or formula (2), the molar ratio of the unit structure having the partial structure represented by formula (1) or formula (2) to the entire polymer is 1 to 100 mol%, preferably 10 to 100 mol%. The unit structure having the partial structure represented by formula (1) or formula (2) may be one type or two or more types.
[0082] In the case where the polymer is a copolymer having a unit structure having a partial structure other than that represented by formula (1) or formula (2), the molar ratio thereof is the remainder of the portion occupied by the unit structure having the partial structure represented by formula (1) or formula (2) relative to the whole copolymer. In the above case, the unit structure having a partial structure other than that represented by formula (1) or formula (2) may be one or more.
[0083] Furthermore, examples of the compound or polymer having the partial structure represented by the above formula (1) include:
[0084] A reaction product (D) or an epoxy compound obtained by reacting an epoxy compound or resin represented by the following formula (B) with a proton-generating compound represented by the following formula (C), or
[0085] The ring-opening reaction product (E) of the resin (C).
[0086] Examples of the epoxy compound (B) include glycidyl ether compounds, glycidyl ester compounds, glycidyl group-containing isocyanurates, epoxycyclohexyl compounds, epoxy-substituted cyclohexyl compounds, and resins thereof. Examples of the epoxy compound (B) used in the present invention are shown below.
[0087]
[0088] Formula (B-1) is available as TEPIC-SS, a product of Nissan Chemical Industries, Ltd.
[0089] Formula (B-2) is available as MA-DGIC manufactured by Shikoku Chemical Industry Co., Ltd.
[0090] Formula (B-3) is available as a product of Nagase Chem-Tech Co., Ltd. under the trade name EX-411.
[0091] Formula (B-4) is available as a product of Nagase Chemtech Co., Ltd. under the trade name EX-521.
[0092] Formula (B-7) is available as RE-810NM manufactured by Nippon Kayaku Co., Ltd.
[0093] Formula (B-8) is available as BATG, a product of Showa Denko K.K.
[0094] Formula (B-9) is available as a product of Nagase Chem-Tech Co., Ltd. under the trade name EX-711.
[0095] Formula (B-10) is available as a product of DIC Corporation under the trade name YD-4032D.
[0096] Formula (B-11) is available as HP-4770, a product of DIC Corporation.
[0097] Formula (B-12) is available as Nippon Steel & Sumitomo Metal Chemical Co., Ltd. under the trade name YH-434L.
[0098] Formula (B-13) is available as EPICLON HP-4700, a product of DIC Corporation.
[0099] Formula (B-14) is available as TEP-G, a product of Asahi Organic Materials Industries, Ltd.
[0100] Formula (B-15) is manufactured by Daicel Corporation and is trade name Epilide GT401. a, b, c, and d are each 0 or 1, and a+b+c+d=1.
[0101] Formula (B-16) is available as EHPE-3150, a product of Daicel Corporation.
[0102] Formula (B-17) is available as a product of DIC Corporation under the trade name HP-7200L.
[0103] Formula (B-18) is available as EPPN-201 manufactured by Nippon Kayaku Co., Ltd.
[0104] Formula (B-19) is available as ECN-1229, a product of Asahi Kasei Epochi Corporation.
[0105] Formula (B-20) is available as EPPN-501H manufactured by Nippon Kayaku Co., Ltd.
[0106] Formula (B-21) is available as NC-2000L, manufactured by Nippon Kayaku Co., Ltd.
[0107] Formula (B-22) is available as NC-3000L, manufactured by Nippon Kayaku Co., Ltd.
[0108] Formula (B-23) is available as NC-7000L, manufactured by Nippon Kayaku Co., Ltd.
[0109] Formula (B-24) is available as NC-7300L, manufactured by Nippon Kayaku Co., Ltd.
[0110] Formula (B-25) is available as NC-3500, a product of Nippon Kayaku Co., Ltd.
[0111] Formula (B-26) is available as EPICLON HP-5000, a product of DIC Corporation.
[0112] Formula (B-27) is available as FAE-2500 manufactured by Nippon Kayaku Co., Ltd.
[0113] Formula (B-28) is available as NC-6000, a product of Nippon Kayaku Co., Ltd.
[0114] In addition, the proton-generating compound (C) may include, for example, a compound containing a phenolic hydroxyl group, a compound containing a carboxylic acid, a compound containing an amine, a compound containing a thiol, or a compound containing an imide, which is capable of reacting with an epoxy group. The proton-generating compound (C) used in the present invention may be exemplified as follows.
[0115]
[0116] Specific examples of the reaction product (D) of the epoxy compound or resin (B) which is a compound or polymer having a partial structure represented by the above formula (1) and the proton-generating compound (C) include the following, but are not limited thereto.
[0117]
[0118] Specific examples of the ring-opening reaction product (E) of the epoxy compound which is a compound or polymer having a partial structure represented by the above formula (1) include the following, but are not limited thereto.
[0119]
[0120] Furthermore, the compound or polymer having the partial structure represented by the above formula (1) is a compound containing a phenolic hydroxyl group, a compound containing a carboxylic acid, a compound containing an amine, a compound containing a thiol, or a compound containing an imide, or a reaction product (F) of a resin thereof with glycidol. Specific examples of the reaction product (F) include the following, but are not limited thereto.
[0121]
[0122] In addition, the compound or polymer having the partial structure represented by the above formula (2) can be exemplified by the reaction product (G) obtained by the above-mentioned epoxy compound or resin represented by the above formula (B) and the proton-generating compound represented by the following formula (H). The proton-generating compound (H) used in the present invention can be exemplified as follows.
[0123]
[0124] Furthermore, specific examples of the reactant (G) obtained from the epoxy compound or resin (B) and the proton-generating compound (H), which is a compound or polymer having a partial structure represented by the above formula (2), include the following, but are not limited to these.
[0125]
[0126] [Crosslinking agent]
[0127] The resist underlayer film forming composition of the present invention may include a crosslinking agent component. As the crosslinking agent, melamine system, substituted urea system, or polymer system thereof, etc. may be cited. Preferably, the crosslinking agent has at least two crosslinking substituents, such as methoxymethylated glycoluril, butoxymethylated glycoluril, methoxymethylated melamine, butoxymethylated melamine, methoxymethylated benzoguanamine, butoxymethylated benzoguanamine, methoxymethylated urea, butoxymethylated urea, methoxymethylated thiourea, or methoxymethylated thiourea. In addition, condensates of these compounds may also be used.
[0128] In addition, as the crosslinking agent, a crosslinking agent with high heat resistance can be used. As the crosslinking agent with high heat resistance, a compound containing a crosslinking-forming substituent having an aromatic ring (for example, a benzene ring or a naphthalene ring) in the molecule can be used.
[0129] Examples of the compound include a compound having a partial structure of the following formula (5-1) and a polymer or oligomer having a repeating unit of the following formula (5-2).
[0130]
[0131] The above R 11 , R12 , R 13 , and R 14 It is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and the alkyl groups exemplified above can be used.
[0132] m1 is 1≤m1≤6-m2, m2 is 1≤m2≤5, m3 is 1≤m3≤4-m2, and m4 is 1≤m4≤3.
[0133] Examples of the compounds, polymers, and oligomers of formula (5-1) and formula (5-2) are shown below.
[0134]
[0135] The above compounds can be obtained as products of Asahi Organic Materials Industries, Ltd. and Honshu Chemical Industries, Ltd. For example, the compound of formula (6-22) among the above crosslinking agents can be obtained as TMOM-BP from Asahi Organic Materials Industries, Ltd.
[0136] The amount of the crosslinking agent added varies depending on the coating solvent used, the base substrate used, the required solution viscosity, the required film shape, etc., but is 0.001 to 80% by weight, preferably 0.01 to 50% by weight, and more preferably 0.1 to 40% by weight relative to the total solid content of the protective film-forming composition. These crosslinking agents may also undergo a crosslinking reaction caused by self-condensation, but when there is a crosslinking substituent in the above-mentioned polymer of the present invention, a crosslinking reaction may occur with these crosslinking substituents.
[0137] [Cross-linking catalyst]
[0138] In order to promote the crosslinking reaction, the protective film forming composition of the present invention may contain a crosslinking catalyst as an optional component. As the crosslinking catalyst, in addition to acidic compounds and basic compounds, compounds that generate acid or base by heat may also be used, but a crosslinking acid catalyst is preferred. As the acidic compound, a sulfonic acid compound or a carboxylic acid compound may be used, and as the compound that generates acid by heat, a thermal acid generator may be used.
[0139] Examples of the sulfonic acid compound or carboxylic acid compound include p-toluenesulfonic acid, trifluoromethanesulfonic acid, pyridine Trifluoromethanesulfonate, pyridine - p-Toluenesulfonate, salicylic acid, camphorsulfonic acid, 5-sulfosalicylic acid, 4-chlorobenzenesulfonic acid, 4-hydroxybenzenesulfonic acid, pyridine -4-Hydroxybenzenesulfonic acid, benzene disulfonic acid, 1-naphthalenesulfonic acid, 4-nitrobenzenesulfonic acid, citric acid, benzoic acid, hydroxybenzoic acid.
[0140] Examples of the thermal acid generator include K-PURE [registered trademark] CXC-1612, K-PURE CXC-1614, K-PURE TAG-2172, K-PURE TAG-2179, K-PURE TAG-2678, and K-PURE TAG2689 (all manufactured by King Industries), and SI-45, SI-60, SI-80, SI-100, SI-110, and SI-150 (all manufactured by Sanshin Chemical Industry Co., Ltd.).
[0141] These crosslinking catalysts may be used alone or in combination of two or more. In addition, as the basic compound, an amine compound or an ammonium hydroxide compound may be used, and as the compound that generates a base by heat, urea may be used.
[0142] As the amine compound, for example, tertiary amines such as triethanolamine, tributanolamine, trimethylamine, triethylamine, tri-n-propylamine, triisopropylamine, tri-n-butylamine, tri-tert-butylamine, tri-n-octylamine, triisopropanolamine, phenyldiethanolamine, stearyldiethanolamine, and diazabicyclooctane, and aromatic amines such as pyridine and 4-dimethylaminopyridine can be mentioned. In addition, primary amines such as benzylamine and n-butylamine, and secondary amines such as diethylamine and di-n-butylamine can also be mentioned as the amine compound. These amine compounds can be used alone or in combination of two or more.
[0143] Examples of the ammonium hydroxide compound include tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, benzyltriethylammonium hydroxide, cetyltrimethylammonium hydroxide, phenyltrimethylammonium hydroxide, and phenyltriethylammonium hydroxide.
[0144] In addition, as the compound that generates a base by heat, for example, a compound having a thermally unstable group such as an amide group, a carbamate group or an aziridine group, which generates an amine by heating, can be used. In addition, urea, benzyltrimethylammonium chloride, benzyltriethylammonium chloride, benzyldimethylphenylammonium chloride, benzyldodecyldimethylammonium chloride, benzyltributylammonium chloride, and choline chloride can also be cited as the compound that generates a base by heat.
[0145] When the protective film forming composition contains a crosslinking catalyst, the content thereof is 0.0001 to 20% by weight, preferably 0.01 to 15% by weight, and more preferably 0.1 to 10% by weight, based on the total solid content of the protective film forming composition.
[0146] [Surfactant]
[0147] In order to improve the coating property on the semiconductor substrate, the protective film forming composition of the present invention may contain a surfactant as an optional component. Examples of the surfactant include polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, polyoxyethylene oleyl ether and other polyoxyethylene alkyl ethers, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether and other polyoxyethylene alkyl aryl ethers, polyoxyethylene / polyoxypropylene block copolymers, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, Sorbitan fatty acid esters such as sorbitan trioleate and sorbitan tristearate, polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan trioleate and polyoxyethylene sorbitan tristearate, etc., nonionic surfactants, EFTOP (registered trademark) EF30 1. EFT EF303, EFT EF352 (Mitsubishi Mitsubishi Electronics Co., Ltd. Co., Ltd.), メガファック [registered trademark] F171, メガファック F173, メガファックR -30、メガファックR-30N、メガファックR-40、メガファックR-40-L M (manufactured by DIC Co., Ltd.), Fluoro FC430, Fluoro FC431 (Sumitomo Solar Fluorine-based surfactants such as SURFLUO® (manufactured by Asahi Glass Co., Ltd.), ASHIGADO (registered trademark) AG710, S-382 (registered trademark), S-101, S-102, S-103, S-104, S-105, and S-106 (manufactured by Asahi Glass Co., Ltd.), and organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.). These surfactants may be used alone or in combination of two or more. When the protective film-forming composition contains a surfactant, the content thereof is 0.0001 to 10% by weight, preferably 0.01 to 5% by weight, relative to the total solid content of the protective film-forming composition.
[0148] [Solvent]
[0149] The protective film-forming composition of the present invention can be prepared by dissolving the above-mentioned components in an organic solvent and used in a uniform solution state.
[0150] As the solvent for the protective film forming composition of the present invention, any solvent that can dissolve the compound containing at least one set of two adjacent hydroxyl groups in the molecule or a polymer thereof can be used without particular limitation. In particular, since the protective film forming composition of the present invention is used in a uniform solution state, it is recommended to use a solvent generally used in a photolithography process in combination in consideration of its coating performance.
[0151] Examples of the organic solvent include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, methyl cellosolve acetate, ethyl cellosolve acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monomethyl ether acetate, propylene glycol propyl ether acetate, toluene, xylene, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, cycloheptanone, 4-methyl-2-pentanol, and 2-hydroxyisobutyric acid. Methyl ester, ethyl 2-hydroxyisobutyrate, ethyl ethoxylate, 2-hydroxyethyl acetate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, 2-heptanone, methoxycyclopentane, anisole, γ-butyrolactone, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide. These solvents can be used alone or in combination of two or more.
[0152] Among these solvents, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ethyl lactate, butyl lactate, and cyclohexanone are preferred. Propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate are particularly preferred.
[0153] [Other ingredients]
[0154] The protective film forming composition of the present invention may contain a light absorber, a rheology regulator, an adhesion aid, etc. The rheology regulator is effective in improving the fluidity of the protective film forming composition. The adhesion aid is effective in improving the adhesion between the semiconductor substrate or the resist and the underlying film.
[0155] As the light absorber, for example, commercially available light absorbers described in "Industrial Colorant Technology and Market" (published by CMC) and "Dye Handbook" (edited by the Society of Synthetic Organic Chemistry) can be suitably used, such as CI Disperse Yellow 1, 3, 4, 5, 7, 8, 13, 23, 31, 49, 50, 51, 54, 60, 64, 66, 68, 79, 82, 88, 90, 93, 102, 114 and 124; CI Disperse Orange 1, 5, 13, 25, 29, 30, 31, 44, 57, 72 and 73; CI Disperse Red 1, 5, 7, 13, 17, 19, 43, 50, 54, 58, 65, 72, 73, 88, 117, 137, 143, 199 and 210; CI Disperse Violet 43; CI Disperse Blue 96; CI Fluorescent Brightener 112, 135 and 163; CI Solvent Orange 2 and 45; CI Solvent Red 1, 3, 8, 23, 24, 25, 27 and 49; CI Pigment Green 10; CI Pigment Brown 2, etc. The light absorber is usually blended in a ratio of 10% by mass or less, preferably 5% by mass or less, based on the total solid content of the protective film-forming composition.
[0156] The rheology modifier is mainly added to improve the fluidity of the protective film forming composition, especially in the baking process, to improve the uniformity of the film thickness of the resist lower film and the filling property of the protective film forming composition into the hole. As a specific example, phthalic acid derivatives such as dimethyl phthalate, diethyl phthalate, diisobutyl phthalate, dihexyl phthalate, butyl isodecyl phthalate, di-n-butyl adipate, diisobutyl adipate, diisooctyl adipate, octyl decyl adipate, di-n-butyl maleate, diethyl maleate, dinonyl maleate and other maleic acid derivatives, oleic acid derivatives such as methyl oleate, butyl oleate, tetrahydrofurfuryl oleate, or stearic acid derivatives such as n-butyl stearate and glyceryl stearate can be cited. These rheology modifiers are usually matched in a ratio of less than 30% by mass relative to the total solid content of the protective film forming composition.
[0157] The adhesion aid is mainly added for the purpose of improving the adhesion between the substrate or the resist and the protective film-forming composition, and in particular, for the purpose of preventing the resist from peeling off during development. Specific examples include chlorosilanes such as trimethylchlorosilane, dimethylhydroxymethylchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane; alkoxysilanes such as trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylhydroxymethylethoxysilane, diphenyldimethoxysilane, and phenyltriethoxysilane; silazanes such as hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyltrimethylsilylamine, and trimethylsilylimidazole; silanes such as hydroxymethyltrichlorosilane, γ-chloropropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-glycidoxypropyltrimethoxysilane; benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, and 2-mercaptobenzothiazole. Heterocyclic compounds such as azole, urea, thiouracil, mercaptoimidazole, and mercaptopyrimidine, urea such as 1,1-dimethylurea and 1,3-dimethylurea, or thiourea compounds. These adhesion aids are usually blended in a ratio of less than 5% by mass, preferably less than 2% by mass, relative to the total solid content of the protective film forming composition.
[0158] [Protective film forming composition]
[0159] The solid content of the protective film forming composition of the present invention is usually 0.1 to 70% by mass, preferably 0.1 to 60% by mass. The solid content is the content ratio of all components after removing the solvent from the protective film forming composition. The proportion of the polymer in the solid content is preferably in the order of 1 to 100% by mass, 1 to 99.9% by mass, 50 to 99.9% by mass, 50 to 95% by mass, and 50 to 90% by mass.
[0160] [Substrate with resist pattern and method for manufacturing semiconductor device]
[0161] Hereinafter, a method for producing a substrate with a resist pattern and a method for producing a semiconductor device using the protective film-forming composition according to the present invention will be described.
[0162] The substrate with a resist pattern according to the present invention can be produced by applying the protective film-forming composition on a semiconductor substrate and firing the coating.
[0163] Examples of the semiconductor substrate to which the protective film-forming composition of the present invention is applied include silicon wafers, germanium wafers, and compound semiconductor wafers such as gallium arsenide, indium phosphide, gallium nitride, indium nitride, and aluminum nitride.
[0164] When a semiconductor substrate having an inorganic film formed on the surface is used, the inorganic film can be formed, for example, by ALD (atomic layer deposition) method, CVD (chemical vapor deposition) method, reactive sputtering method, ion plating method, vacuum evaporation method, spin coating method (spin-on glass: SOG). Examples of the inorganic film include polycrystalline silicon film, silicon oxide film, silicon nitride film, BPSG (Boro-Phospho Silicate Glass) film, titanium nitride film, titanium oxide nitride film, tungsten film, gallium nitride film, and gallium arsenide film.
[0165] On such a semiconductor substrate, the protective film forming composition of the present invention is applied by a suitable coating method such as a spin coater or a coater. Then, a protective film is formed by baking using a heating device such as a hot plate. As baking conditions, it is appropriately selected from a baking temperature of 100°C to 400°C and a baking time of 0.3 minutes to 60 minutes. Preferably, the baking temperature is 120°C to 350°C, the baking time is 0.5 minutes to 30 minutes, and more preferably, the baking temperature is 150°C to 300°C, and the baking time is 0.8 minutes to 10 minutes. As the film thickness of the protective film formed, for example, it is 0.001μm to 10μm, preferably 0.002μm to 1μm, and more preferably 0.005μm to 0.5μm. When the temperature during baking is lower than the above range, crosslinking sometimes becomes insufficient, and it is not easy to obtain the resistance of the formed protective film to the resist solvent or the alkaline hydrogen peroxide aqueous solution. On the other hand, when the temperature during baking is higher than the above range, the protective film is sometimes decomposed by heat.
[0166] Exposure is performed through a mask (photomask) for forming a prescribed pattern, using, for example, i-rays, KrF excimer lasers, ArF excimer lasers, EUV (extreme ultraviolet rays) or EB (electron beams). An alkaline developer is used for development, and is appropriately selected from a development temperature of 5°C to 50°C and a development time of 10 seconds to 300 seconds. As an alkaline developer, an aqueous solution of an alkali such as sodium hydroxide, potassium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, ammonia water, etc., a primary amine such as ethylamine, n-propylamine, a secondary amine such as diethylamine, di-n-butylamine, a tertiary amine such as triethylamine, methyldiethylamine, etc., an alcohol amine such as dimethylethanolamine, triethanolamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, quaternary ammonium salts such as choline, cyclic amines such as pyrrole and piperidine, etc. can be used. Furthermore, an appropriate amount of an alcohol such as isopropyl alcohol, a nonionic surfactant, etc. can also be added to the aqueous solution of the above-mentioned alkali and used. Among them, preferred developing solutions are quaternary ammonium salts, and more preferably tetramethylammonium hydroxide and choline. Furthermore, surfactants and the like may be added to these developing solutions. Instead of alkaline developing solutions, a method may be used in which the portion of the photoresist whose alkali dissolution rate is not increased is developed by using an organic solvent such as butyl acetate.
[0167] Next, the protective film is dry-etched using the formed resist pattern as a mask. At this time, if the inorganic film is formed on the surface of the semiconductor substrate used, the surface of the inorganic film is exposed, and if the inorganic film is not formed on the surface of the semiconductor substrate used, the surface of the semiconductor substrate is exposed.
[0168] Furthermore, a desired pattern is formed by performing wet etching using a semiconductor wet etching solution using the protective film after dry etching (when a resist pattern remains on the protective film, the resist pattern is also used) as a mask.
[0169] As the semiconductor wet etching solution, a general chemical solution used for etching a semiconductor wafer can be used, and for example, either an acidic substance or an alkaline substance can be used.
[0170] Examples of the acidic substance include hydrogen peroxide, hydrofluoric acid, ammonium fluoride, acidic ammonium fluoride, ammonium hydrogen fluoride, buffered hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and a mixed solution thereof.
[0171] As a substance showing alkalinity, an alkaline hydrogen peroxide solution obtained by mixing an organic amine such as ammonia, sodium hydroxide, potassium hydroxide, sodium cyanide, potassium cyanide, triethanolamine, etc. with hydrogen peroxide solution to make the pH alkaline can be cited. As a specific example, SC-1 (ammonia-hydrogen peroxide solution) can be cited. In addition, a substance that can make the pH alkaline can also be used as a wet etching solution. The substance that can make the pH alkaline is, for example, a substance that mixes urea with hydrogen peroxide solution, and heats the mixture to cause thermal decomposition of urea to generate ammonia, and finally makes the pH alkaline.
[0172] Among them, acidic hydrogen peroxide water or alkaline hydrogen peroxide water is preferred, and alkaline hydrogen peroxide water is particularly preferred.
[0173] These liquids may contain additives such as surfactants.
[0174] The use temperature of the semiconductor wet etching solution is preferably 25° C. to 90° C., more preferably 40° C. to 80° C. The wet etching time is preferably 0.5 minute to 30 minutes, more preferably 1 minute to 20 minutes.
[0175] Example
[0176] The present invention will be described in further detail below with reference to Examples etc., but the present invention is not limited to the following Examples etc. at all.
[0177] The apparatus and the like used for measuring the weight average molecular weight of the polymer obtained in the following synthesis example are shown.
[0178] Device: HLC-8320GPC manufactured by Higashikata Co., Ltd.
[0179] GPC column: Shodex〔registered trademark〕Asahipak〔registered trademark〕(Showa Denko K.K.)
[0180] Column temperature: 40°C
[0181] Flow rate: 0.6mL / min
[0182] Eluent: N,N-dimethylformamide (DMF)
[0183] Standard sample: Polystyrene (Tosoh Corporation)
[0184] <Example 1>
[0185] A solution of 7.00 g of glycerol monomethacrylate (product name: Brenma GLM, manufactured by NOF Corporation), 2.01 g of 2,2'-azobis(methyl isobutyrate), and 28.84 g of propylene glycol monomethyl ether was placed in a dropping funnel, and added dropwise to a reaction flask containing 7.21 g of propylene glycol monomethyl ether at 100° C. under a nitrogen atmosphere, and heated and stirred for 17 hours. 9 g of a cation exchange resin (product name: Dauexe [registered trademark] 550A, manufactured by Muromachi Technos Co., Ltd.) and 9 g of an anion exchange resin (product name: Anvalite [registered trademark] 15JWET, manufactured by Organo Co., Ltd.) were added to the resulting solution, and ion exchange treatment was performed at room temperature for 4 hours. The resin solution corresponding to the formula (X-1) was obtained by separation with an ion exchange resin. The weight average molecular weight Mw measured by GPC in terms of polystyrene was 3,400.
[0186]
[0187] 5.18 g of the obtained resin solution (solid content: 15.9 wt%), 0.21 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent, and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.02 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 8.20 g of propylene glycol monomethyl ether, and 1.40 g of propylene glycol monomethyl ether acetate.
[0188] <Example 2>
[0189] Pyridine was added as a crosslinking acid catalyst to 5.18 g of a resin solution (solid content: 15.90 wt%) corresponding to formula (X-1). A solution of a protective film-forming composition was prepared by adding 0.05 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 7.27 g of propylene glycol monomethyl ether, and 1.40 g of propylene glycol monomethyl ether acetate.
[0190] <Example 3>
[0191] A solution of 6.00 g of glycerol monomethacrylate (product name: Brenma GLM, manufactured by NOF Corporation), 3.75 g of methyl methacrylate, 0.62 g of 2,2'-azobis(isobutyronitrile), and 33.17 g of propylene glycol monomethyl ether was placed in a dropping funnel, and added dropwise to a reaction flask containing 8.29 g of propylene glycol monomethyl ether at 100° C. under a nitrogen atmosphere, and heated and stirred for 17 hours. 10 g of a cation exchange resin (product name: Dauexe [registered trademark] 550A, manufactured by Muromachi Technos Co., Ltd.) and 10 g of an anion exchange resin (product name: Anvalite [registered trademark] 15JWET, manufactured by Organo Co., Ltd.) were added to the resulting solution, and ion exchange treatment was performed at room temperature for 4 hours. The resin solution corresponding to the formula (X-2) was obtained by separation with an ion exchange resin. The weight average molecular weight Mw measured by GPC in terms of polystyrene was 9,900.
[0192]
[0193] To 6.27 g of the obtained resin solution (solid content: 17.49 wt%), 0.27 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent and 0.27 g of pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.03 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 11.56 g of propylene glycol monomethyl ether, and 1.86 g of propylene glycol monomethyl ether acetate.
[0194] <Example 4>
[0195] Pyridine was added as a crosslinking acid catalyst to 7.62 g of a resin solution (solid content: 17.49 wt%) corresponding to formula (X-2). A solution of a protective film-forming composition was prepared by adding 0.07 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 10.46 g of propylene glycol monomethyl ether, and 1.86 g of propylene glycol monomethyl ether acetate.
[0196] <Example 5>
[0197] A solution of 4.50 g of glycerol monomethacrylate (product name: Brenma GLM, manufactured by NOF Corporation), 6.13 g of polyethylene glycol monomethacrylate (product name: Brenma PE-90, manufactured by NOF Corporation), 0.54 g of 2,2'-azobis(isobutyronitrile), and 35.75 g of propylene glycol monomethyl ether was added to a dropping funnel, and the mixture was added dropwise to a reaction flask containing 8.94 g of propylene glycol monomethyl ether at 100° C. under a nitrogen atmosphere, followed by heating and stirring for 17 hours. To the obtained solution, 11 g of a cation exchange resin (product name: Dawuex [registered trademark] 550A, Muromachi Technos Co., Ltd.) and 11 g of an anion exchange resin (product name: Anvalite [registered trademark] 15JWET, Organo Co., Ltd.) were added, and ion exchange treatment was performed at room temperature for 4 hours. The ion exchange resin was separated to obtain a resin solution corresponding to formula (X-3), and the weight average molecular weight Mw measured by GPC in terms of polystyrene was 11,500.
[0198]
[0199] To 6.38 g of the obtained resin solution (solid content: 17.19 wt%), 0.27 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.03 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 11.45 g of propylene glycol monomethyl ether, and 1.86 g of propylene glycol monomethyl ether acetate.
[0200] <Example 6>
[0201] Pyridine was added as a crosslinking acid catalyst to 7.75 g of a resin solution (solid content: 17.19 wt%) corresponding to formula (X-3). A solution of a protective film-forming composition was prepared by adding 0.07 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 10.32 g of propylene glycol monomethyl ether, and 1.86 g of propylene glycol monomethyl ether acetate.
[0202] <Example 7>
[0203] A solution of 9.36 g of 2-carboxyethyl acrylate, 6.50 g of methyl methacrylate, 1.25 g of 2,2'-azobis(isobutyronitrile), and 54.74 g of propylene glycol monomethyl ether was added to a dropping funnel, and added dropwise to a reaction flask containing 13.68 g of propylene glycol monomethyl ether at 100°C under a nitrogen atmosphere, and heated and stirred for 17 hours. 2.25 g of glycidol, ethyltriphenylphosphine bromide, and 40.00 g of the obtained solution were added. 0.28g, 10.12g of propylene glycol monomethyl ether, heated under reflux and stirred for 21 hours. 11g of cation exchange resin (product name: Dawuex [registered trademark] 550A, Muromachi Technos Co., Ltd.) and 11g of anion exchange resin (product name: Anvalite [registered trademark] 15JWET, Organo Co., Ltd.) were added to the obtained solution, and ion exchange treatment was performed at room temperature for 4 hours. The ion exchange resin was separated to obtain a resin solution equivalent to formula (X-4), and the weight average molecular weight Mw measured by GPC in terms of polystyrene was 15000.
[0204]
[0205] To 5.05 g of the obtained resin solution (solid content: 16.31 wt%), 0.21 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.02 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 5.54 g of propylene glycol monomethyl ether, and 4.19 g of propylene glycol monomethyl ether acetate.
[0206] <Example 8>
[0207] Pyridine was added as a crosslinking acid catalyst to 5.95 g of a resin solution (solid content: 16.31 wt%) corresponding to formula (X-4). A solution of a protective film-forming composition was prepared by adding 0.05 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 4.81 g of propylene glycol monomethyl ether, and 4.19 g of propylene glycol monomethyl ether acetate.
[0208] <Example 9>
[0209] A solution of 16.00 g of glycidyl methacrylate, 4.53 g of 2,2'-azobis(isobutyronitrile), and 65.68 g of propylene glycol monomethyl ether was added to a dropping funnel, and added dropwise to a reaction flask containing 16.48 g of propylene glycol monomethyl ether at 100°C under a nitrogen atmosphere, and heated and stirred for 13 hours. 30.00 g of the obtained solution (epoxy value 676 g / eq), 3.72 g of α-thioglycerol, and ethyltriphenylphosphine bromide were added. 0.32g, 12.05g of propylene glycol monomethyl ether, heated under reflux and stirred for 17 hours under a nitrogen atmosphere. 9g of cation exchange resin (product name: Dawuex [registered trademark] 550A, Muromachi Technos Co., Ltd.) and 9g of anion exchange resin (product name: Anvalite [registered trademark] 15JWET, Organo Co., Ltd.) were added to the obtained solution, and ion exchange treatment was performed at room temperature for 4 hours. The ion exchange resin was separated to obtain a resin solution equivalent to formula (X-5), and the weight average molecular weight Mw measured by GPC in terms of polystyrene was 9700.
[0210]
[0211] To 5.80 g of the obtained resin solution (solid content: 18.93 wt%), 0.27 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.03 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 12.04 g of propylene glycol monomethyl ether, and 1.86 g of propylene glycol monomethyl ether acetate.
[0212] <Example 10>
[0213] Pyridine was added as a crosslinking acid catalyst to 7.04 g of a resin solution (solid content: 18.93 wt%) corresponding to formula (X-5). A solution of a protective film-forming composition was prepared by adding 0.07 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 11.04 g of propylene glycol monomethyl ether, and 1.86 g of propylene glycol monomethyl ether acetate.
[0214] <Comparative Example 1>
[0215] A solution of 16.00 g of 2-hydroxyethyl methacrylate, 1.18 g of 2,2'-azobis(isobutyronitrile), and 54.98 g of propylene glycol monomethyl ether was placed in a dropping funnel, and added dropwise to a reaction flask containing 13.75 g of propylene glycol monomethyl ether at 100° C. under a nitrogen atmosphere, and heated and stirred for 21 hours. 17 g of a cation exchange resin (product name: Dauexe [registered trademark] 550A, Muromachi Technos Co., Ltd.) and 17 g of an anion exchange resin (product name: Anvalite [registered trademark] 15JWET, Organo Co., Ltd.) were added to the resulting solution, and ion exchange treatment was performed at room temperature for 4 hours. The resin solution corresponding to the formula (Y-1) was obtained by separation with an ion exchange resin. The weight average molecular weight Mw measured by GPC in terms of polystyrene was 6,800.
[0216]
[0217] To 4.63 g of the obtained resin solution (solid content: 17.76 wt%), 0.21 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.02 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 5.95 g of propylene glycol monomethyl ether, and 4.19 g of propylene glycol monomethyl ether acetate.
[0218] <Comparative Example 2>
[0219] Pyridine was added as a crosslinking acid catalyst to 7.36 g of a resin solution (solid content: 17.76 wt%) corresponding to formula (Y-1). A solution of a protective film-forming composition was prepared by adding 0.07 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 6.99 g of propylene glycol monomethyl ether, and 5.59 g of propylene glycol monomethyl ether acetate.
[0220] <Comparative Example 3>
[0221] A solution of 6.50 g of 2-hydroxyethyl methacrylate, 5.00 g of methyl methacrylate, 0.96 g of 2,2'-azobis(isobutyronitrile), and 39.87 g of propylene glycol monomethyl ether was placed in a dropping funnel, and added dropwise to a reaction flask containing 9.97 g of propylene glycol monomethyl ether at 100° C. under a nitrogen atmosphere, and heated and stirred for 17 hours. 12 g of a cation exchange resin (product name: Dauexe [registered trademark] 550A, Muromachi Technos Co., Ltd.) and 12 g of an anion exchange resin (product name: Anvalite [registered trademark] 15JWET, Organo Co., Ltd.) were added to the resulting solution, and ion exchange treatment was performed at room temperature for 4 hours. The resin solution corresponding to the formula (Y-2) was obtained by separation with an ion exchange resin. The weight average molecular weight Mw measured by GPC in terms of polystyrene was 4,900.
[0222]
[0223] To 4.60 g of the obtained resin solution (solid content: 17.88 wt%), 0.21 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.02 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 5.99 g of propylene glycol monomethyl ether, and 4.19 g of propylene glycol monomethyl ether acetate.
[0224] <Comparative Example 4>
[0225] Pyridine was added as a crosslinking acid catalyst to 7.45 g of a resin solution (solid content: 17.88 wt%) corresponding to formula (Y-2). A solution of a protective film-forming composition was prepared by adding 0.07 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 6.90 g of propylene glycol monomethyl ether, and 5.58 g of propylene glycol monomethyl ether acetate.
[0226] <Comparative Example 5>
[0227] A solution of 14.00 g of 4-hydroxyphenyl methacrylate (product name: PQMA, manufactured by Showa Denko K.K.), 1.13 g of 2,2'-azobis(isobutyronitrile), and 42.37 g of propylene glycol monomethyl ether was placed in a dropping funnel, and added dropwise to a reaction flask containing 18.16 g of propylene glycol monomethyl ether at 100° C. under a nitrogen atmosphere, and heated and stirred for 14 hours. 15 g of a cation exchange resin (product name: Dauexe [registered trademark] 550A, manufactured by Muromachi Technos Co., Ltd.) and 15 g of an anion exchange resin (product name: Anvalite [registered trademark] 15JWET, manufactured by Organo Co., Ltd.) were added to the resulting solution, and ion exchange treatment was performed at room temperature for 4 hours. The resin solution corresponding to the formula (Y-3) was obtained by separation with an ion exchange resin. The weight average molecular weight Mw measured by GPC in terms of polystyrene was 11,000.
[0228]
[0229] To 4.47 g of the obtained resin solution (solid content: 18.41 wt%), 0.21 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.02 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 6.12 g of propylene glycol monomethyl ether, and 4.19 g of propylene glycol monomethyl ether acetate.
[0230] <Comparative Example 6>
[0231] Pyridine was added as a crosslinking acid catalyst to 7.24 g of a resin solution (solid content: 18.41 wt%) corresponding to formula (Y-3). A solution of a protective film-forming composition was prepared by adding 0.07 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 7.12 g of propylene glycol monomethyl ether, and 5.58 g of propylene glycol monomethyl ether acetate.
[0232] <Comparative Example 7>
[0233] 0.82 g of poly(p-hydroxystyrene) (product name: VP-8000, manufactured by Nippon Soda Co., Ltd.), 0.21 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Nippon Science Industries Co., Ltd.) as a crosslinking agent, and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.03 g of p-toluenesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 9.77 g of propylene glycol monomethyl ether, and 4.19 g of propylene glycol monomethyl ether acetate.
[0234] <Comparative Example 8>
[0235] 1.33 g of poly(p-hydroxystyrene) (product name: VP-8000, manufactured by Nippon Soda Co., Ltd.) and pyridine as a crosslinking acid catalyst were added. A solution of a protective film-forming composition was prepared by adding 0.07 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 13.02 g of propylene glycol monomethyl ether, and 5.58 g of propylene glycol monomethyl ether acetate.
[0236] <Comparative Example 9>
[0237] A solution of 16.00 g of glycidyl methacrylate, 4.53 g of 2,2'-azobis(isobutyronitrile), and 65.68 g of propylene glycol monomethyl ether was added to a dropping funnel, and added dropwise to a reaction flask containing 16.48 g of propylene glycol monomethyl ether at 100° C. under a nitrogen atmosphere, and heated and stirred for 13 hours. 5.31 g of 3,4-dihydroxybenzoic acid, 0.20 g of benzyltriethylammonium chloride, and 17.89 g of propylene glycol monomethyl ether were added to 30.00 g of the resulting solution (epoxy value 676 g / eq), and heated and refluxed for 20 hours under a nitrogen atmosphere. To the obtained solution, 11 g of a cation exchange resin (product name: Dawuex [registered trademark] 550A, Muromachi Technos Co., Ltd.) and 11 g of an anion exchange resin (product name: Anvalite [registered trademark] 15JWET, Organo Co., Ltd.) were added, and ion exchange treatment was performed at room temperature for 4 hours. The ion exchange resin was separated to obtain a resin solution corresponding to formula (Y-4), and the weight average molecular weight Mw measured by GPC in terms of polystyrene was 24,400.
[0238]
[0239] To 4.22 g of the obtained resin solution (solid content: 19.51 wt%), 0.21 g of tetramethoxymethyl glycoluril (product name: POWDERLINK [registered trademark] 1174, manufactured by Japan Science Instruments Co., Ltd.) as a crosslinking agent and pyridine as a crosslinking acid catalyst were added. - 0.03 g of p-toluenesulfonate, 0.001 g of surfactant (manufactured by DIC Corporation, product name: Megafac [trade name] R-40, a fluorine-based surfactant), 9.12 g of propylene glycol monomethyl ether, and 1.40 g of propylene glycol monomethyl ether acetate were used to prepare a solution of a protective film-forming composition.
[0240] <Comparative Example 10>
[0241] Pyridine was added as a crosslinking acid catalyst to 6.83 g of a resin solution (solid content: 19.51 wt%) corresponding to formula (Y-4). A solution of a protective film-forming composition was prepared by adding 0.07 g of trifluoromethanesulfonate, 0.001 g of a surfactant (manufactured by DIC Corporation, product name: Megafac R-40, a fluorine-based surfactant), 11.24 g of propylene glycol monomethyl ether, and 1.86 g of propylene glycol monomethyl ether acetate.
[0242] [Resist solvent resistance test]
[0243] The protective film forming compositions prepared in Examples 1 to 10 and Comparative Examples 1 to 10 were each applied (spin-coated) on a silicon wafer using a spin coater. The coated silicon wafer was heated on a hot plate at 215°C for 1 minute to form a film (protective film) with a thickness of 200 nm. Next, in order to confirm the resist solvent resistance of the protective film, the silicon wafer after the protective film was formed was immersed in a solvent obtained by mixing propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate in a weight ratio of 7:3 for 1 minute, and then baked at 100°C for 30 seconds after spin drying. The film thickness of the protective film before and after immersion in the mixed solvent was measured by an optical interference film thickness meter.
[0244] The evaluation of the solvent resistance of the resist was performed by calculating the film thickness reduction rate (%) of the protective film removed by solvent immersion using the formula ((film thickness before solvent immersion) - (film thickness after solvent immersion)) ÷ (film thickness before solvent immersion) × 100. It should be noted that if the film thickness reduction rate is about 1% or less, it can be said to be within the allowable range.
[0245] [Table 1]
[0246] 〔Table 1〕
[0247]
[0248] According to the above results, even after being immersed in a resist solvent, the film thickness change of Examples 1 to 10 was very small, showing good resist solvent resistance. On the other hand, Comparative Examples 6 and 10 were removed by immersion in a resist solvent, and did not show sufficient resist solvent resistance. Therefore, Examples 1 to 10 are useful for expressing resist solvent resistance and have sufficient resist solvent resistance to function as a protective film.
[0249] [Resistance test to alkaline hydrogen peroxide solution]
[0250] As an evaluation of resistance to alkaline hydrogen peroxide water, the protective film forming compositions prepared in Examples 1 to 10, Comparative Examples 1 to 5, Comparative Example 7, Comparative Example 9 and Comparative Example 10, which showed good resist solvent resistance in the above-mentioned resist solvent resistance test, were each applied to a TiN vapor-deposited substrate with a film thickness of 50 nm, and heated at 215°C for 1 minute to form a film with a film thickness of 200 nm. Next, 28% ammonia water, 33% hydrogen peroxide, and water were mixed in a weight ratio of 1:1:2 to prepare alkaline hydrogen peroxide water. The TiN vapor-deposited substrate coated with the protective film forming composition was immersed in the alkaline hydrogen peroxide water heated to 50°C, and the time from just after immersion to the protective film peeling off from the substrate was measured. The results are shown in Table 2.
[0251] [Table 2]
[0252] 〔Table 2〕
[0253]
[0254] According to the above results, Examples 1 to 10 show that the coating film is less likely to peel off from the substrate in alkaline hydrogen peroxide water than Comparative Examples 1 to 5 and Comparative Example 7. That is, Examples 1 to 10 show good liquid resistance to alkaline hydrogen peroxide water compared to Comparative Examples 1 to 5 and Comparative Example 7, and are useful as a protective film against alkaline hydrogen peroxide water.
[0255] [Evaluation of Etching Selectivity]
[0256] As an evaluation of the etching selectivity, the protective film-forming compositions prepared in the above-mentioned Examples 2, 4, 6, 8, 10, and Comparative Example 10 were each coated on a silicon wafer and heated at 215° C. for 1 minute to form a film with a film thickness of 200 nm. Next, the formed protective film and the resist film obtained from the resist solution (product name: Sumire JSTO PAR855) manufactured by Sumoco Chemical Co., Ltd. were dry-etched by a mixed gas of oxygen and nitrogen using a dry etching apparatus (RIE-10NR) manufactured by Sumco Co., Ltd., thereby measuring the ratio of the dry etching rate of the protective film to the resist (dry etching rate selectivity). The etching selectivity is shown in Table 3.
[0257] [Table 3]
[0258] 〔Table 3〕
[0259]
[0260] According to the above results, Examples 2, 4, 6, 8, and 10 have higher dry etching selectivity than Comparative Example 10. That is, Examples 2, 4, 6, 8, and 10 have faster dry etching speeds than Comparative Example 10, and can shorten the dry etching time required to remove the protective film, which is useful for reducing damage to the base substrate.
[0261] Industrial Availability
[0262] According to the present invention, a protective film-forming composition which has both a wet etching mask function (SC-1 resistance) during base substrate processing and can be quickly removed by dry etching (high etching rate) can be provided.
Claims
1. A composition for forming a protective film resistant to a wet etching solution for semiconductors, comprising: a polymer of a compound containing at least one set of two hydroxyl groups adjacent to each other in the molecule; a solvent; a crosslinking catalyst; and a surfactant, The polymer is a homopolymer, and is composed only of a unit structure having a partial structure represented by formula (1) or formula (2). In formula (1) and formula (2), R 1 , R 2 and R 3 Each of them is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms which may be substituted, or an aryl group having 6 to 40 carbon atoms which may be substituted, and R 1 Can be used with R 2 or R 3 Together they form a ring, Z 1 and Z 2 It is a monovalent organic group derived from an acrylic acid-based polymer or a methacrylic acid-based polymer.
2. A composition for forming a protective film resistant to a wet etching solution for semiconductors, comprising: a polymer of a compound containing at least one set of two hydroxyl groups adjacent to each other in the molecule; a solvent; a crosslinking catalyst; and a surfactant, The polymer is a copolymer containing one or more unit structures having a partial structure represented by formula (1) or formula (2) and a unit structure having a partial structure other than formula (1) or formula (2). It is an addition polymer made from an addition polymerizable monomer selected from acrylic acid, methacrylic acid, acrylate compounds, methacrylate compounds, acrylamide compounds, methacrylamide compounds, vinyl compounds, styrene compounds, maleimide compounds, maleic anhydride and acrylonitrile, In formula (1) and formula (2), R 1 , R 2 and R 3 Each of them is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms which may be substituted, or an aryl group having 6 to 40 carbon atoms which may be substituted, and R 1 Can be used with R 2 or R 3 Together they form a ring, Z 1 and Z 2 It is a monovalent organic group derived from an acrylic acid-based polymer or a methacrylic acid-based polymer.
3. The protective film-forming composition according to claim 1 or 2, wherein in the formula (1) and the formula (2), R 1 , R 2 and R 3 A hydrogen atom. The protective film-forming composition according to claim 1 or 2, further comprising a crosslinking agent.
5. A protective film, characterized in that: A fired product of a coating film formed from the protective film-forming composition according to any one of claims 1 to 4.
6. A method for manufacturing a substrate with a resist pattern, characterized in that: The method comprises the steps of applying the protective film composition according to any one of claims 1 to 4 on a semiconductor substrate and firing the composition to form a protective film as a resist underlayer film, and is used for the production of a semiconductor.
7. A method for manufacturing a semiconductor device, comprising the following steps: forming a protective film on a semiconductor substrate on which an inorganic film can be formed using the protective film-forming composition described in any one of claims 1 to 4, forming a resist pattern on the protective film, dry-etching the protective film using the resist pattern as a mask to expose the surface of the inorganic film or the semiconductor substrate, and wet-etching and washing the inorganic film or the semiconductor substrate using a semiconductor wet etching solution using the dry-etched protective film as a mask.
Citation Information
Patent Citations
JP1975041175A
Coating composition for use with overcoated photoresist
JP2017107185A
Coating compositions for use with overcoated photoresist
JP2017187764A
New anthracene derivative
JP1995082221A
Positive type resist laminated body
JP2001147538A